ECOTOURISM IN DISASTER-PRONE CONSERVATION AREAS AND ITS UNDERLYING GOVERNANCE: A CASE STUDY IN THE MOUNT MERAPI NATIONAL PARK - Marwedhi Nurratyo; Arief Rosyidie; Constanza Parra Novoa (Centre For Tourism Planning and Development, 2014)
Mass tourism is criticized because it jeopardizes environment, economic, socio-integrity of tourism destinations, and it can lead to impoverishment of local societies. Ecotourism emerges as an alternative of tourism which is more environmentally friendly and offers inclusion of social responsibility. This research aims to assess whether the ecotourism practices in disaster-prone conservation area fulfil the ideal ecotourism criteria and to explain the importance of governance in realising ecotourism practices. The result showed that ecotourism practices in the Merapi area are insufficient to fulfil ideal ecotourism criteria. It is found that quality of communication and collaboration, political views and character of planning (reactive or adaptive) determine the practice of ecotourism.